Developing and Evaluating the Le-Zoo Board: An Augmented Reality-Based Medium for English Vocabulary Reading among Students with Autism - Yunita Putri Maulidina; Testiana Deni Wijayatiningsih; Dodi Mulyadi (Universitas Islam Negeri Palopo, 2026)
Students with autism may benefit from structured, visually clear, and multisensory English learning materials. This study developed and preliminarily evaluated the Le-Zoo Board, an interactive learning medium integrating a board game, sensory audio, and augmented reality cards for English animal-vocabulary reading. The study employed a research-and-development approach based on the ADDIE model. Participants were 11 students with mild autism from a special school in Yogyakarta, selected through purposive sampling. Data were collected through material- and media-expert validation, a one-group pre-test–post-test, and a student-response questionnaire. Material-expert validation reached 97.6%, and media-expert validation reached 97%, both categorized as very valid. The paired-samples analysis showed a significant pre–post difference (mean difference = -44.545, SD = 9.342, t(10) = -15.815, p < .001). The student-response score was 480 of 550, or 87.27% of the maximum possible score, indicating a positive practicality response. These findings provide preliminary evidence that the Le-Zoo Board is valid, positively received, and associated with short-term improvement in English animal-vocabulary reading. Because the study involved a small one-group sample, causal and comparative interpretations should be made cautiously.